2014
DOI: 10.4314/ahs.v14i3.35
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties studies of trunk barks of terminalia ivorensis (Combretaceae), a commercial and medicinal specie, on some methicillin-resistant Staphylococci spp strains.

Abstract: Abstract:Background: Methicillin-resistant Staphylococcus aureus, Staphylococcus epidermidis and coagulase-negative Staphylococcus infections are a worldwide concern. Terminalia ivorensis, of Combretaceae family plant, is widely used traditional medicinal in Côte d'Ivoire to treat dermal diseases (affection in which Staphylococci are implied) including local inflammation and also to treat voice-loss. Objectives: This study focused to investigate the effect in vitro of the extracts of trunk barks of Terminalia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Other Terminalia spp. and members of the Combretaceae family have been found to have anti-bacterial [ 42 ] and anti-trypanosomal compounds [ 43 ], suggesting that these plants could be of importance in modern pharmacology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other Terminalia spp. and members of the Combretaceae family have been found to have anti-bacterial [ 42 ] and anti-trypanosomal compounds [ 43 ], suggesting that these plants could be of importance in modern pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of treatments for ECF and sweating sickness were said to depend on the stage of the disease. Often, traditional treatments are viewed as just as effective as modern medicine [ 51 ] and indeed laboratory experiments have confirmed the efficacy of certain plant families against bacteria and protozoans in vitro [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Falodun et al suggested that the Persea americana plant is effective on both fungi and bacteria (81). The petroleum ether extract of the plant has an excellent antibacterial activity against MRSA with an IC50 value of 7.8 μg/mL (82).…”
Section: Family Lauraceaementioning
confidence: 99%
“…Terminalia ivorensis also plays a major role in increasing soil fertility where fall off leaves are decomposed and add more nutrients to the soil [2]. This species is widely used for medicinal purposes in Africa [3,4]. This tree species if protected from logger can attain heights of up to 50 m and girth of 500 cm.…”
Section: Introductionmentioning
confidence: 99%